Physicochemical, microbiological and sensory properties of low fat yoghurt fortified with carrot powder - Madora, Eshmail P.; Takalani, Thakhani K.; Mashau, Mpho E. (International Journal of Agricultural and Biological Engineering, 2016)
Yoghurt is considered as a healthy food and incorporating carrot powder will make it even healthier. Carrot powder is a good source of beta carotene and provitamin A. The objective of this study was to determine the effects of adding carrot powder on the physicochemical, microbiological and sensory properties of low fat plain yoghurt. Plain and carrot yoghurt were prepared in the laboratory scale production using low fat milk. Carrot yoghurt was prepared by blending low fat milk with 1%, 2% and 3% carrot powder before fermentation. Physicochemical analysis revealed a decrease in pH value and an increase in titratable acidity, viscosity and total soluble solids with the increase of carrot powder. On the other hand, protein content decreased with the increase of carrot powder. In terms of the lightness (L*) and the redness (a*), 3% carrot yoghurt had low values of lightness while it had higher values of redness. Microbial count showed the significant difference between the 3% carrot yoghurt and 1% and 2% carrot yoghurt. There was a significant difference on the sensory scores of colour and aroma of carrot yoghurt and plain yoghurt as the carrot yoghurt got higher scores than plain yoghurt. There was no significant difference (p<0.05) between the acceptability of the plain yoghurt, 1% and 2% carrot yoghurt and a significant difference was there between 3%. Thus, fortifying yoghurt with 1% and 2% carrot powder produced acceptable yoghurt with beneficial health effects.Keywords: yoghurt, physicochemical property, beta carotene, provitamin A, carrot powderDOI: 10.3965/j.ijabe.20160901.1874Citation: Madora E P, Takalani T K, Mashau M E. Physicochemical, microbiological and sensory properties of low fat yoghurt fortified with carrot powder. Int J Agric & Biol Eng, 2016; 9(1): 118-124.